Geriatric assessment in elderly patients receiving oral anticoagulants: results of the nursing study. (14th October 2021) - Tsareva, I; Vorobyeva, N; Semochkina, G; Kotovskaya, Y; Tkacheva, O
Abstract: Background: It is well known that thrombosis and bleeding risk increases with age, in the same time prevalence of geriatric syndromes increases too. It can influence negatively on efficacy and safety of anticoagulant therapy. However, impact of geriatric syndromes is often underestimated in clinical practice. Purpose: To evaluate prevalence of geriatric syndromes in elderly patients receiving oral anticoagulants (OAC). Methods: This study enrolled 510 patients (19% male) aged 75–100 (mean 82±4) years hospitalized to our clinic consecutively from June to November in 2019. Nurses examined all patients according to specially designed nursing assessment algorithm that included Mini-Cog test, Morse Fall and Norton scales, Barthel Activities of daily living Index, Short Physical Performance Battery (SPPB) tests, Mini Nutritional Assessment (MNA) scale, Geriatric Depression Scale (GDS-15), and some other questionnaires. Before hospitalization, 61 patients (12%) received OAC due to atrial fibrillation (AF) (83, 6%), venous thromboembolism (VTE) (9, 8%) and AF+VTE (6, 6%). In all patients, AF frequency was 21% (n=107), but OAC were prescribed in 51% (n=55) only. Patients receiving OAC (group 1; n=61) did not differ from those without OAC (group 2; n=449) by age, sex, frequency of hypertension, previous myocardial infarction and revascularization, stable angina, and some other chronic diseases. Results: Patients in group 1 had lower score on Norton scale (17, 2±2, 3 vs 18, 1±1, 8; p=0, 001), Barthel Index (87, 9±19, 1 vs 94, 4±10, 7; p<0, 001), SPPB (4, 5±3, 1 vs 6, 0±3, 3; p=0, 001), walk speed (0, 50±0, 44 vs 0, 60±0, 30 m/s; p=0, 014) and higher score on Morse Fall scale (47, 8±20, 7 vs 39, 8±20, 6; p=0, 005) compared to patients in group 2. They had higher frequency of frailty (SPPB tests ≤7 score) (82% vs 66%; p=0, 011), functional dependence (Barthel Index ≤60 score) (71% vs 44%; p<0, 001) and pressure ulcers high risk (Norton scale ≤13 score) (6, 6% vs 1, 6%; p=0, 012). They also had higher frequency of fall in the past year (57% vs 41%; p=0, 017), high fall risk (Morse Fall scale ≥51 score) (38% vs 28%; p=0, 073) and subcutaneous hematomas (25% vs 12%; p=0, 009). Univariate regression analysis with age and sex adjustment showed that patients receiving OAC had higher risk of functional dependence (OR 3, 05; 95% CI 1, 69–5, 49; p<0, 001), frailty (OR 2, 31; 95% CI 1, 16–4, 62; p=0, 018) and pressure ulcers high risk (OR 4, 24; 95% CI 1, 19–15, 16; p=0, 026). OAC therapy was also associated with falls in the past year (OR 1, 94; 95% CI 1, 13–3, 35; p=0, 016) Conclusion: Patients receiving OAC had a higher incidence of some geriatric syndromes, such as frailty, functional dependence, falls, pressure ulcers high risk, and lower functional status compared to patients without OAC. Nursing assessment of geriatric patients provides physician with additional data that allows to identify factors potentially affecting the efficacy and safety of OAC therapy. Funding Acknowledgement: Type of funding sources: None.